Wajah terbuka dan hidup tertutup: Gender dan seksualiti dalam karya sastera Melayu Riau pinggir abad ke 19 - Ding, Choo Ming (Universiti Kebangsaan Malaysia, 2006)
Himpunan Gunawan Bagi Laki-Laki dan Perempuan is a manual of love magic. It is almost exclusively for women’s use, despite its title that it is addressed to men and women. Written by Khatijah Terung, who is believed to have been born on Pulau Penyengat in 1885. She was most likely a commoner, though her true origins were unknown. She married Raja Haji Abdullah bin Raja Hassan to be his fourth wife. It is said that his curiosity about Khatijah’s reputation as an adept in magic that attracted him to her when she was in the service of his third wife, Cik Yam. She tells us nothing of how she learned her art, apart from a brief acknowledgement that one spell was given to her by a Wan Mah. Nevertheless, her work bears the stamp of her individuality. She celebrates the value of good conjugal relations to women. Four fifths of the book are devoted to means to enhance sexual relations within marriage